2020
DOI: 10.1007/s40200-020-00652-8
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of physiotherapy interventions in mitigating the symptoms and complications of diabetic peripheral neuropathy: A systematic review

Abstract: Purpose Diabetic peripheral neuropathy (DPN) leads to decreased sole sensation and balance disorder, all of which increase the risk of falls and socioeconomic costs. Since the physiotherapists do not use the same manner to lessen the complications of this problem. Therefore, this review study was directed to appraise physiotherapy intervention efficiencies in diminishing DPN's symptoms and complications. Method A database search of Pubmed, Elsevier, Google Scholar, and Embase was performed to determine DPN's p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 63 publications
0
9
0
4
Order By: Relevance
“…Microvascular abnormalities, metabolic cascades, end products activated by hyperglycemia, inflammatory processes, oxidative stress, and cellular factors in patients with DM cause decreased blood flow, ischemia, and edema within the nerve [ 20 28 29 ], resulting in demyelination and axonal damage, also referred to as DPN [ 19 30 ]. The present study showed that in the diabetic group the axons of the sciatic nerve were obviously atrophic, demyelination was observed, and some myelinated fibers displayed Wallerian degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microvascular abnormalities, metabolic cascades, end products activated by hyperglycemia, inflammatory processes, oxidative stress, and cellular factors in patients with DM cause decreased blood flow, ischemia, and edema within the nerve [ 20 28 29 ], resulting in demyelination and axonal damage, also referred to as DPN [ 19 30 ]. The present study showed that in the diabetic group the axons of the sciatic nerve were obviously atrophic, demyelination was observed, and some myelinated fibers displayed Wallerian degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Viscoelasticity is an essential feature of biological tissues, including nerves that possess both viscous and elastic properties [ 18 ]. Furthermore, it was confirmed that microvascular abnormalities and inflammation are involved in the pathogenesis of DPN [ 19 20 21 ]. Therefore, the viscosity of nerves may be an important index for the detection of DPN.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging technologies, pharmacology and therapeutics such as exercise therapy, electrotherapy, and other physiotherapy methods, exercise therapy has been the most effective. 14 Studies have shown that supervised exercise improves cardiorespiratory function, innervation, [15][16][17] nerve conduction, 18 muscle strength, balance, 19 and reduces pain interference. 20 However, the effects of exercise on key DPN markers such as lower extremity muscle adiposity, nerve microarchitecture, and muscle metabolism have yet to be reported.…”
Section: Significance Of This Studymentioning
confidence: 99%
“…Plantar ulceration and amputation, the disease's most fatal outcome, can still be avoided if proper measures are applied. 4 …”
Section: Introductionmentioning
confidence: 99%